CFD analysis of efficiency and pressure drop in a gas-solid square cyclones separator - NOVI SYLVIA; . YUNARD; . ELWINA; . WUSNAH; YAZID BINDAR (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
In this paper, two small cyclones with the same hydraulic diameter and volume, which one is square and the other one is round (Lapple cyclone), are numerically compared. A pre-processor software GAMBIT was employed to set up the configuration, discretisation, and boundary conditions of the cyclone. The characteristics of the cyclone being studied was 0.2 m in diameter, receiving a gas flow rate of 0.1 m3/s with a particle mass loading of 0.01 kg/s. A commercial CFD code FLUENT 6.2.16 was employed to simulate the flow field and particle dynamics in the cyclone. The Reynolds averaged Navier–Stokes equations with Reynolds Stress Turbulence Model (RSTM) are solved by use of the finite volume method based on the SIMPLE pressure correction algorithm in the computational domain. The Eulerian–Lagrangian computational procedure is used to predict particles tracking in the cyclones. The velocity fluctuations are simulated using the Discrete Random Walk (DRW).The results show that collection efficiency of square cyclone is the better with increasing flow rate than round cyclone. The pressure drop in square cyclone is higher than the pressure drop in small round one.